Early Antiretroviral Therapy in AIDS Patients Presenting With Toxoplasma gondii Encephalitis Is Associated With More Sequelae but Not Increased Mortality - Cubas-Vega, Nadia; López Del-Tejo, Paola; Baia-da-Silva, Djane C.; Sampaio, Vanderson Souza; Jardim, Bruno Araújo; Santana, Monique Freire; Lima Ferreira, Luiz Carlos; Safe, Izabella Picinin; Alexandre, Márcia A. Araújo; Lacerda, Marcus Vinícius Guimarães; Monteiro, Wuelton Marcelo; Val, Fernando (Frontiers in Medicine, 2022)
Background: Evidence on the optimal time to initiate antiretroviral therapy (ART) in the presence of neurotoxoplasmosis (NTX) is scarce. We compared the impact of early versus delayed ART initiation on mortality and neurologic complications at discharge in a Brazilian population co-infected with HIV and NTX. Methods: We retrospectively evaluated data from 9 years of hospitalizations at a referral center in Manaus, Amazonas. All ART-naïve hospitalized patients were divided into early initiation treatment (EIT) (0-4 weeks) and delayed initiation treatment (DIT) (>4 weeks). The groups were compared using chi-square test and mortality at 16 weeks. Results: 469 patients were included, including 357 (76.1%) in the EIT group. The median CD4+ lymphocyte count and CD4+/CD8+ ratio were 53 cells/mm3 and 0.09, respectively. Mortality rate and presence of sequelae were 4.9% (n=23) and 41.6% (n=195), respectively. Mortality was similar between groups (p=0.18), although the EIT group had the highest prevalence of sequelae at discharge (p=0.04). The hazard ratio for death at 16 weeks with DIT was 2.3 (p=0.18). The necessity for intensive care unit admission, mechanical ventilation, and cardiopulmonary resuscitation were similar between groups. Conclusion: In patients with AIDS and NTX, early ART initiation might have a detrimental influence on the occurrence of sequelae.